Moderating effect of attitude and perception on adoption of safer sex practices amongst students in tertiary institutions in Anambra State (2013)
Attitude and perception strongly predict the adoption of safer sexual practices. Descriptive Survey Design was adopted to examine the moderating effect of attitude and perception of students in tertiary institutions in Anambra state on the adoption of safer sexual practices. Two thousand, five hundred and fifty respondents (Male=1,150 Female= 1,400) with age range of 16 to 28 years (x =20.05; SD=3.6) were drawn from an estimated students population of 25,250 using Stratified Sampling Technique. Two research questions and two hypotheses guided the study. A 22 item self- report questionnaire was used for data collection. Multiple Regression and t-test were used to analyze the data at 0.05 level of significance. Attitude and perception have a joint contribution of 61 % of the variance in dependent variable. However, perception made more potent contribution (Beta= .0.331; t= 3.11; P= <.05) than attitude (Beta= .117; t=2.04; P<.05). Gender and socio-economic background also have significant contribution. There is need for Counsellors in tertiary institutions to mount intensive and comprehensive reproductive health campaign messages that systematically incorporate beliefs, knowledge, attitude and subjective norms to effectively persuade and promote behaviour change among the students.